A REVIEW ON HEPATOPROTECTIVE PLANTS AND COMPOUNDS (International Association of Biologicals and Computational Digest, 2022)
.The liver is one of the most significant organs in the body, executing a fundamental role in the regulation of diverse processes, among which the metabolism, secretion, storage, and detoxification of endogenous and exogenous substances are noticeable. Due to these functions, hepatic diseases have become threat to public health, and they remain as major worldwide issue. Despite enormous advances in modern medicine, there are no completely effective drugs that stimulate hepatic function, that offer complete protection of the organ, or that help to regenerate hepatic cells. Thus, it is necessary to identify pharmaceutical alternatives for the treatment of liver diseases, with the aim of these alternatives being more effective and less toxic. The use of many herbs or their extracts for treatment of various ailments has been documented in Ayurvedic medical system. The immense potential of medicinal plants used in traditional systems has been well recognized and documented in recent years. Numerous plants and polyherbal formulations are used for the treatment of liver diseases. Phytotherapeutic approach to modern drug development can provide many invaluable drugs from traditional medicinal plants. Search for pure phytochemicals as drugs is time consuming and expensive. This review article is going to enumerate some plants with hepatoprotective properties and it is going to provide a robust insight into the phytochemistry, medicinal uses and pharmacology of a few hepatoprotective plants and their compounds. Nonetheless, further study on the phytochemistry and mechanism of action of the pure compounds are necessary to fully understand the phytochemical profile and the complex pharmacological effects of this plant.
Keywords: Hepato protective plants, Andrographis Paniculata, Aerva lanata, Andrographolide.